PRODUKTIVITAS ITIK (ANAS DOMESTICUS) PETELUR DENGAN SUPLEMENTASI TEPUNG LIMBAH UDANG DALAM PAKAN KOMPLIT - Aji, Bayu Laksono; Rinawidiastuti, Rinawidiastuti; Mudawaroch, Roisu Eny (Jurnal Peternakan Nusantara, 2022)
This study aims to determine that the addition of Shrimp Waste Flour (SWF) can increase the productivity of mojosari ducks. The research was conducted at the mojosari laying duck farm in the Butuh village, District of Purworejo. The experimental livestock used were 60 mojosari ducks with 24 weeks years old, the cattle were placed in 20 colony cage plots, each cage plot filled with 3 ducks. The materials used are Shrimp Waste Flour (SWF) and complete feed. The feed treatment given to the ducks was as follows; P0, P1, P2, P3, P4 containing 0, 2, 4, 6, and 8% SWF, respectively. The method used in this study is the experimental method using a completely randomized design (CRD) consisting of 5 treatments and 4 replications in order to obtain 20 experimental units. Parameters observed were consumption of dry mater and crude protein, drinking consumption, average daily growth of duck, hen day product, conversion and feed efficiency. The data obtained were analyzed using the Analysis of Variance (ANOVA) test, if there is a difference, then the Duncan New Range Test (DMRT) test with a significance level of 5%. The results showed that shrimp waste flour had a significant effect (P<0.05) on consumption dry mater as much as 128.04 g; 121.47 g; 134.96 g and 135.66 g. Consumption crude protein had a significant effect (P<0.05) as much as 14.29%; 14.88%; 15.47%; 10.06% and 16.65%. Drinking water consumption had a significant effect (P<0.05) in the amount of 0.78 l; 0.83 l; 0.93 l; 1.1 l and 1.24 l. Average daily growth of duck had unsignificant effect (P>0.05) of 2.23 g; 2.18 g; 1.76 g; 0.94 g and 1.52 g. Hen day product had unsignificant effect (P>0.05) with a percentage of 49.7%; 53.87%; 54.76%; 57.74% and 49.41%. The feed conversion value had unsignificant effect (P>0.05) with a value of 4.53; 4.05; 4.05; 4.51 and 4.24. Feed efficiency was unsignificantly different (P>0.05) with a percentage of 20.74%; 23.23%; 23.58%; 23.12% and 20.86%. Shrimp waste flour had a significant on consumption of dry mater, crude protein and drinking water, but has unsignificant on average daily growth of duck, hen day product, conversion and feed efficiency. Keywords: Shrimp waste flour, productivity, mojosari duck